2023
DOI: 10.1038/s41598-023-27613-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning models development for shear strength prediction of reinforced concrete beam: a comparative study

Abstract: Fiber reinforced polymer (FPR) bars have been widely used as a substitutional material of steel reinforcement in reinforced concrete elements in corrosion areas. Shear resistance of FRP reinforced concrete element can be affected by concrete properties and transverse FRP stirrups. Hence, studying the shear strength (Vs) mechanism is one of the highly essential for pre-design procedure for reinforced concrete elements. This research examines the ability of three machine learning (ML) models called M5-Tree (M5),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…To obtain an optimised ANN model, the value of "R" should be highest (approaching 1), while the values of "MSE" and "MAE" should be lowest [30]. To overcome the problem of overfitting, the gradient descent methodology is used to converge values of weights and biases, while, at the same time, early stopping criteria, as defined in the functionality of ANN, is employed to avoid overfitting [31][32][33].…”
Section: The Functionality Of the Ann Modelmentioning
confidence: 99%
“…To obtain an optimised ANN model, the value of "R" should be highest (approaching 1), while the values of "MSE" and "MAE" should be lowest [30]. To overcome the problem of overfitting, the gradient descent methodology is used to converge values of weights and biases, while, at the same time, early stopping criteria, as defined in the functionality of ANN, is employed to avoid overfitting [31][32][33].…”
Section: The Functionality Of the Ann Modelmentioning
confidence: 99%
“…The shear capacity of RC beams was predicted mathematically using a variety of ML approaches [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The use of the well-known artificial neural network (ANN) technique was adopted to investigate the impact of various crucial variables on the shear strength of FRP-RC beams [25].…”
Section: Shear Strengthmentioning
confidence: 99%
“…It was shown that the ELM can be utilized to accurately measure the shear strength of compositestrengthened RC beams. In a more recent study [32], the predictive efficacy of three ML methods, namely, ELM, M5-Tree, and RF, was compared using the results on 112 FRPstrengthened RC beams. The results revealed that the M5-Tree model yielded slightly higher accuracy in predicting the shear strength as compared with the other two models.…”
Section: Shear Strengthmentioning
confidence: 99%